An Analysis the Private Sector Life Insurance Compares with Special Reference to HDFC: - (Journal of Advances and Scholarly Researches in Allied Education, 2019)
HDFC is one of the major private sector banks having unique standing among the other financial institutions. It provides a broad variety of goods, facilities distribution capacities under the umbrella product. It has thus made a remarkable contribution to the overall development of the economy. HDFC bank is the India’s largest private sector bank and lender by assets. The major aim of HDFC is provide a wide range of improved financial products services to various sectors of economy, which results in improving and broadening the financial portfolio across customer base. HDFC bank has announced to become a second major private sector bank in India.